Literature Review : Implementation of Effective Cough on Sputum Production in Tuberculosis Patients - Yani Rusi Syarri; Yayang Harigustian; Venny Diana (UrbanGreen, 2022)
Background : Tuberculosis is an infectious disease that can attack the lungs and organs outside the lungs. One of the signs and symptoms of tuberculosis is coughing. Effective cough aims to remove sputum in the airway. Objective: To identify the implementation of effective cough therapy on sputum production in tuberculosis patients. Methods: This study used a literature review method by determining the keywords tuberculosis, effective cough and sputum production. Then an article search was carried out until 3 research articles were found to be analyzed. Result: The results of this study used 3 research articles that matched the inclusion criteria set by the authors. From the results of the analysis of the three research articles used, it is known that the three articles used effective coughing techniques in removing sputum in Tuberculosis patients. Conclusion: From the results of the literature review, it can be seen that the effective cough technique is the right technique in removing sputum